Gravitational Properties of Atom - Orlov, S. (Journal of Advance Research in Applied Science (ISSN 2208-2352), 2016)
The evidence that the strength of any body provide nuclear forces of gravity. The nuclear force of gravity generated by the essential micro vortices. The vortex creates a pressure gradient in the ether. The pressure gradient is the source of nuclear energy. The nuclear force of gravity on the surface of the cores is equal for all elementary particles.